2018
DOI: 10.1038/s41575-018-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic role of vagal afferent innervation

Abstract: The regulation of energy and glucose balance contributes to whole-body metabolic homeostasis, and such metabolic regulation is disrupted in obesity and diabetes. Metabolic homeostasis is orchestrated partly in response to nutrient and vagal-dependent gut-initiated functions. Specifically, the sensory and motor fibres of the vagus nerve transmit intestinal signals to the central nervous system and exert biological and physiological responses. In the past decade, the understanding of the regulation of vagal affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 226 publications
1
66
1
1
Order By: Relevance
“…As such, the infusion of glucose into the upper small intestine stimulates intestinal GLP1 release, as revealed by increased portal vein active GLP1 levels, however, there is no effect on peripheral circulating GLP1 levels. These findings suggest that GLP1 acts locally in the gut by activating GLP1R on vagal afferent nerves that innervate the gut mucosa 153,177 .…”
Section: Metformin Action On the Gut-brain Neuronal Axis Emerging Evmentioning
confidence: 88%
See 1 more Smart Citation
“…As such, the infusion of glucose into the upper small intestine stimulates intestinal GLP1 release, as revealed by increased portal vein active GLP1 levels, however, there is no effect on peripheral circulating GLP1 levels. These findings suggest that GLP1 acts locally in the gut by activating GLP1R on vagal afferent nerves that innervate the gut mucosa 153,177 .…”
Section: Metformin Action On the Gut-brain Neuronal Axis Emerging Evmentioning
confidence: 88%
“…The glucoregulatory role of duodenal AMPK activation was also demonstrated in response to intraduodenal infusion of resveratrol (a natural polyphenolic compound known for its many beneficial effects to human health) or the AMPK activator A-769662, indicating the therapeutic relevance of targeting duodenal AMPK for gut-mediated antidiabetic therapies 155,181,182 . In a recent 2018 study, it was reported that inhibition of mTOR signalling is also required for the glucose-lowering effect of intraduodenal metformin but that mTOR acts independently of AMPK signalling 177 , thereby adding a novel potential gut target to potently lower glucose levels in patients with T2DM.…”
Section: Metformin Action On the Gut-brain Neuronal Axis Emerging Evmentioning
confidence: 99%
“…Sensory signaling through the vagus nerve has a critical role in the maintenance of bodily homeostasis in diverse functions relating to digestion, satiety, respiration, blood pressure, and heart rate control ( Mazzone and Undem, 2016 , Waise et al., 2018 , Wehrwein and Joyner, 2013 ). Its profound role is illustrated by abnormalities that can lead to far-reaching consequences, including gastroesophageal reflux disease, heart failure, failure of respiratory control, gastroparesis, vasovagal syncope, and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…The system is divided into the sympathetic nervous system, which controls "fight-or-flight" responses, and the parasympathetic nervous system, which regulates "rest-and-digest" functions 1 . A main parasympathetic nerve is the vagus nerve, which innervates many visceral organs, such as the heart, lungs, stomach, liver, pancreas and intestines 2,3 , and contributes to the regulation of numerous autonomic functions, which include breathing, immune responses, digestion, glucose metabolism and others [4][5][6][7][8] . The vagus nerve at the cervical level is partially composed of myelinated Aδ and B fibers 9,10 , but the great majority of axons (over 80%) are unmyelinated C-fibers 2,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic nerves are typically dominated by hundreds to thousands of unmyelinated fibers 27,28,38,39 . The fibers of the vagus nerve in particular innervate multiple critical organs and contribute to the regulation of many autonomic functions [2][3][4][5][6][7][8] . Therefore, a need remains for an intraneural electrode array that can record physiological single-neuron activity at multiple sampling locations within small autonomic nerves.…”
Section: Introductionmentioning
confidence: 99%